CLINICAL PATHOPHYSIOLOGY OF PYRUVATE KINASE DEFICIENCY - Поляков, Павел Павлович; Занин, Сергей Александрович; Цирульникова, Софья Владимировна (Medicine in Kuzbass, 2025)
In our review we discuss pyruvate kinase deficiency, which is the most prevalent hereditary hemolytic enzymopathy resulting from a glycolytic defect. This review examines the etiopathogenesis of the disease, which underlies the clinical, laboratory manifestations and therapeutic principles. Energy deficiency impairs the normal activity of the erythrocyte, leading to chronic hemolysis and its consequences, including hemic hypoxia, extramedullary hematopoiesis, secondary hemochromatosis, and gallstone disease.These consequences have a deleterious impact on various systems and organs, manifesting as damage to the nervous system, liver, glands of internal secretion, and mineral and bone disorders. Furthermore, pyruvate deficiency and energy deficiency have an adverse impact on erythroblasts, which may elucidate the phenomenon of ineffective erythropoiesis observed in pyruvate kinase deficiency.The most significant laboratory indicator of the key disease mechanism is a reduction in pyruvate kinase activity. However, this laboratory finding may be affected by a number of confounding factors and may potentially be caused by other disease, such as a KLF1 gene mutation. The allosteric activator of pyruvate kinase, mitapivate, can affect a key disease mechanism. Other therapeutic options include iron chelation and control of folate levels. Splenectomy, which is associated with significant risks of infection and thrombosis, may be considered as a last therapeutic option.
Keywords: pyruvate kinase deficiency; hemolytic anemia; extramedullary hematopoiesis; secondary hemochromatosis; splenectomy; mitapivat